AN EVOLVING MORAL THEOLOGY: SHIFTS IN UNDERSTANDING NATURAL LAW - Astorga, Christina A. (Asian Horizons, 2015)
As moral theology continues to evolve, it reaps many shifts in understanding moral theories, concepts, and praxis. The main inquiry of this paper is how the concept of natural law has evolved in moral theology, and how the new developments in understanding natural law have broken the impasse of the age-long debate between the views of natural law according to nature and natural law according to reason. The new shifts in understanding natural law seek a holistic approach that builds a bridge between the two strains of nature and reason. This results in a rethinking of the pre-rational and biological aspects of natural law, beyond the critique of physicalism levelled against natural law according to nature. The discourse on natural law, however, has gone beyond the debate between nature and reason. The challenge of feminism and global pluralism has brought into critical light new questions about natural law. Having profound implications for the normative criteria of moral judgment, understanding the shifts in the approaches to natural law is central to an evolving moral theology.